ROLE OF DIGITAL TECHNOLOGY IN PHYSICS - Shakhriyor Yolchiyev Husanovich; Saidakhan Mamasodikova Soyibjon's daughter (Journals Park Publishing, 2022)
Physics is the science of understanding nature, stands majestically proclaim in almost every physics classroom. And certainly, in every physics classroom, the most effective way to understand this very nature has always been and remains an experiment. But it is becoming increasingly difficult to interest children in simple physical effects in the era of virtual entertainment and gadgets. This is especially true for such not very innovative sections, such as, for example, Molecular physics and thermodynamics. However, digital technologies open up new opportunities not only for entertainment, but also for education. Therefore, let's try to figure out what modern tools are available to the teacher, who wants to "revive" the standard course of experiments.
Keywords: learning activities,; performance of laboratory work; Informatization of education